2021
DOI: 10.1094/pdis-08-20-1711-re
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Bacteriophages Infecting Burkholderia glumae, the Major Causal Agent of Bacterial Panicle Blight in Rice

Abstract: Bacterial panicle blight (BPB) caused by Burkholderia glumae is one of the most severe seed-borne bacterial diseases of rice in the world, which can decrease rice production by up to 75%. Nevertheless, there are few effective measures to manage this disease. In an attempt to develop an alternative management tool for BPB, we isolated and characterized phages from soil and water that are effective to lyse several strains of B. glumae. After tests of host ranges, the phages NBP1-1, NBP4-7 and NBP4-8 were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Similar studies reveal the existence of bacteriophages from various families, demonstrating the diversity of the isolated phages. Eventhough Burkholderia consists of several species and genomovar, most of the phages isolated are from Myoviridae family as demonstrated in the many studies [46,[53][54][55]. In the current investigation, we could observe that all four phages had an icosahedral head illustrating that they belonged to Straboviridae family.…”
Section: Marrs Et Al (2021)supporting
confidence: 64%
“…Similar studies reveal the existence of bacteriophages from various families, demonstrating the diversity of the isolated phages. Eventhough Burkholderia consists of several species and genomovar, most of the phages isolated are from Myoviridae family as demonstrated in the many studies [46,[53][54][55]. In the current investigation, we could observe that all four phages had an icosahedral head illustrating that they belonged to Straboviridae family.…”
Section: Marrs Et Al (2021)supporting
confidence: 64%
“…They can cause rearrangements and can lead to alterations in the expression of phage-encoded proteins, resulting in the establishment of irreversible lysogeny [35] and the diversification of the bacterial genome architecture, and in many strains, they represent a significant fraction of the strain-specific DNA sequences [34,36]. Remarkably, phages have also been reported as efficient biocontrol agents against B. glumae [37,38]. Thus, investigations on the contribution of these agents in the lifestyle, such as pathogenic and nonpathogenic strains, and the diversity of B. glumae are the subjects of future work.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the bac-terial strains were tested for their ability to induce a hypersensitive response (HR) on tobacco leaves (Nicotiana tabacum cv Xanthi), according to Furuya et al [30], followed by a pathogenicity test on the rice plants. The pathogenicity of the isolates was tested on rice plants (cultivar DOA2), which were obtained according to Jungkhun et al [38] (2021). The plants were inoculated at the tillering stage using a modified method from Pet-amphai et al [10].…”
Section: Hypersensitive Response and Pathogenicity Testmentioning
confidence: 99%
“…Meanwhile, under glasshouse conditions, bacteriophage suspensions have shown notable success in controlling BPB pathogens when sprayed on rice plants at the flowering stage [69,72,73,75]. In 2021 Jungkhun et al [68] also reported that the foliar application of the bacteriophage NBP4-7 reduced the severity of BPB disease caused by B. glumae BGLa14-8 by up to 62% relative to the control. Overall, the application of bacteriophages in controlling BPB pathogens has shown promising results under in vitro and glasshouse conditions.…”
Section: фBurag58mentioning
confidence: 99%
“…The lytic life cycle ends with the lysis protein production that makes the host cell burst [83]. In 2021, bacteriophages from water and soil collected at various locations in Louisiana, USA, showed lysis activity towards BPB pathogens, suggesting its lytic life cycles [68].…”
Section: Bacteriophagesmentioning
confidence: 99%